2011
DOI: 10.1177/0192623311406936
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Phosphorylation of Akt and ERK1/2 in Rat Mammary Gland, Colon, and Liver Following Treatment with Human Insulin and IGF-1

Abstract: High doses of insulin and the insulin analog AspB10 have been reported to increase mammary tumor incidence in female rats likely via receptormediated mechanisms, possibly involving enhanced IGF-1 receptor activation. However, insulin and IGF-1 receptor functionality and intracellular signaling in the rat mammary gland in vivo is essentially unexplored. The authors investigated the effect of a single subcutaneous dose of 600 nmol/ kg human insulin or IGF-1 on Akt and ERK1/2 phosphorylation in rat liver, colon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
(86 reference statements)
2
18
0
Order By: Relevance
“…Such a mechanism is plausible, because Akt is a recognized oncogene, and gain-of-function Akt mutations are involved in many human cancers (Altomare and Testa, 2005). Interestingly, insulin has recently been shown to cause rapid Akt phosphorylation in the rat mammary gland in vivo (Hvid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism is plausible, because Akt is a recognized oncogene, and gain-of-function Akt mutations are involved in many human cancers (Altomare and Testa, 2005). Interestingly, insulin has recently been shown to cause rapid Akt phosphorylation in the rat mammary gland in vivo (Hvid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These cells represent tissue where carcinogenic and growth-promoting effects of insulin have been observed in vivo in rats and mice (Tran et al, 2006;Hvid et al, 2011), as well as the liver, which represents target tissue for the classic metabolic effects of insulin. Therefore, cells such as these are considered relevant for inclusion in cell panels for preclinical safety assessment of new insulin analogues.…”
Section: Introductionmentioning
confidence: 99%
“…injection of a 4 nmol/kg dose (Ikeda et al ., 2009). In addition, the s.c. injection of a supraphysiological dose (600 nmol/kg) of IGF-1 increased Akt phosphorylation in liver, colon and mammary gland of Sprague–Dawley rats (Hvid et al ., 2011). Akt and ERK phosphorylation also occurred in mouse mammary gland tissue only after a large bolus tail vein injection of IGF-1 (Lee et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The insulin and IGF receptors trigger a complex range of intracellular signals for metabolism, cell growth and proliferation [16]. Their relative abundance affects intracellular signalling and has important consequences for tissue-specific responses to insulin, IGFs and insulin analogues [17, 18]. In addition, it has been demonstrated that overexpression of IR and IGF1R in human breast carcinomas allows insulin and IGF-1 hybrid receptors to form.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been performed in mice [39, 40]. The one rat study that has been reported to date used suprapharmacological doses and only investigated downstream signalling [17]. …”
Section: Discussionmentioning
confidence: 99%